Communicative-pragmatic direction in the study of phraseological units and their derivatives in French and Uzbek. - Nortoeva Nodira Muhammadalievna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article discusses the communicative-pragmatic aspects of phraseological units are studied in linguistics, and they are considered as a certain tool in creating the socio-psychological aspects of the language